Use of galvanic vestibular stimulation device as a countermeasure for microgravity effects in spaceflight - Soto, Enrique; Vega, Rosario (Frontiers in Space Technologies, 2024)
This work discusses the challenges of space exploration, focusing on microgravity-induced physiological changes, particularly those affecting the vestibular system, which significantly alters human performance in space, necessitating effective countermeasures. In microgravity, astronauts experience disorientation and space motion sickness due to changes in vestibular input, leading to symptoms like vertigo and headache. Postflight, astronauts show various neurological changes, similar to symptoms in individuals with vestibular disorders experiencing 2 significant cognitive and perceptual difficulties. Studies have also shown that microgravity affects cortical and sensory responses, altering perception, motor function, and brain connectivity. Galvanic Vestibular Stimulation (GVS) is explored as a countermeasure, using modulated electrical currents to evoke neuronal activity in vestibular end-organs, potentially stabilizing posture and gaze in microgravity. The work proposes that GVS could serve as a noninvasive intervention to help adapt to space environments by enhancing vestibular function and possibly aiding cognitive functions and underscores the need for continued research into the vestibular system's role in human health and performance during space missions. It highlights the potential of GVS as a promising countermeasure for the challenges posed by microgravity.